Tourist mobility of Polish residents in the context of the COVID-19 pandemic - Matczak, Andrzej; Szymańska, Daniela (Bulletin of Geography. Socio-economic Series, 2022)
The purpose of this study is to identify the impact that the COVID-19 pandemic had on the tourism sector in Poland in terms of the tourist mobility of Poles, i.e., on the volume and nature of tourist trips of Polish residents. It is based on a comparison of the numbers and natures of tourist trips made during the pandemic (2020–21) against the preceding period (2018–19). This study is based on data from Statistics Poland collected from several hundred thousand participants (an average of over 136,000 people surveyed annually). The study discusses changes in: Polish residents’ level of participation in tourist trips; the number and breakdown of tourist trips; and the reasons/purposes for tourist trips. In addition, changes in the breakdown of transport used during tourist trips are shown. Changes observed in tourist travel expenses from 2018 to 2021 are also discussed. Another subject of our analysis is changes in tourist travel destinations and the seasonality of these trips.